Prophecy's last word an exposition of the Revelation - Tatford, Frederick Albert, 1901- (London, UK Pickering and Inglis, 1947)
Includes bibliographical references and indexes.
Brethren writer. Donated by Mr J. Biden, Student, 1960.
Keywords: Bible. N.T. Revelation -- commentaries